The Identity Construction Through Music Notation of The Indigenous Style of Gitar Tunggal Lampung Pesisir - Hidayatullah, Riyan; Jazuli, Muhammad; Syarif, Muhammad Ibnan (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This study aims to reveal the meaning of music notation writing of gitar tunggal Lampung Pesisir written by Imam Rozali. Imam is a gitar tunggal player who wrote his technique and playing style in notation symbols. This article uses a case study research design with pattern matching techniques (Yin, 2018). Data were collected through observation, interviews, document analysis, and audio recordings. A series of tests were carried out on the notation and other supporting information to improve the validity of the data. Laboratory analysis was carried out to describe signs, interpret symbols, and compare Western musical notation. As a result, (1) the music notation written by Imam Rozali is a musical expression used as a medium for remembering; (2) the writing of Imam Rozali’s musical notation constructs his musical identity as a Gitar tunggal Lampung Pesisir player; (3) Imam Rozali’s music notation symbolizes an indigenous style which has its concept of gitar tunggal music; (4) Imam Rozali tries to add value to his musical identity among gitar tunggal players because the notation is a symbol of intellectuality.